Abstract Number ‐ 238: More Rapid Anticoagulation is Safe for Cerebral Sinus Thrombosis Patients and Shortens ICU Stays - Anish Deshmukh; Gitanjali Das; Adam de Havenon; Vivek Reddy; Matthew D Alexander (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Cerebral sinus thrombosis (CST) can often prove challenging to manage effectively. Anticoagulation is the accepted first‐line therapy for treatment, but heterogeneity exists among treatment protocols. Anecdotally, delays in achieving therapeutic anticoagulation seem to prolong treatment courses and may lead to worse outcomes. Furthermore, delays in identifying the subset of patients not responding to medical therapy may preclude some patients from endovascular therapy who would otherwise be candidates but miss the therapeutic window. However, justifiable safety concerns often limit the speed with which anticoagulation targets are sought. This study examines the impact of time needed to achieve a therapeutic response to anticoagulation on hospitalization and clinical outcomes among patients admitted with symptomatic CST. Methods Patients admitted with CST at a single academic medical center between January 2020 and June 2022 were identified. Those with CST related to trauma, tumor, sepsis, or COVID infection were excluded. Date of admission, demographic factors, clinical status including neurological examination, and anticoagulation regimen were noted. The duration required to reach the therapeutic anticoagulation goal, defined according to partial thromboplastin time or anti‐Xa levels, was noted by measuring the time from commencement of anticoagulation therapy and the first lab result within the therapeutic range. The primary outcome was independence at discharge, which was determined by modified Rankin scale (mRS). Additional outcomes were determined by measuring ICU admission duration and mRS at discharge, thirty days, and ninety days. These were calculated with linear correlation and the Wilcoxon rank sum test, respectively. Additionally, an a priori multivariable model was constructed with covariates of age, gender, presence of neurological deficits at presentation, and presence of intracranial hemorrhage. To this base model, the binary variable of achievement of anticoagulation goal within 48 hours was added. Results No significant relationship was noted between time to therapeutic anticoagulation and mRS at discharge (p = 0.099), thirty days (p = 0.784), or ninety days (p = 0.931). Time required to achieve therapeutic anticoagulation was positively correlated with duration of ICU admission (r2 = 0.148, p = 0.013). In the multivariable model, functional status at discharge was largely driven by the admission neurological examination (p = 0.014). Among patients with neurological deficits, 66.7% were functionally independent at discharge, whereas this occurred in 95.7% of patients with a normal neurological examination at admission. For the base multivariable model, the area under the receiver operator curve was 0.895. Addition of the 48‐hour anticoagulation goal achievement variable increased it to 0.923 (p = 0.196). In the adjusted model, an odds ratio of 3.80 was identified for achieving independence at discharge (p = 0.280). Conclusions In patients admitted with CST, longer times required to achieve therapeutic anticoagulation are associated with prolonged ICU stays. More aggressive anticoagulation demonstrated no deleterious effects, and achieving anticoagulation goal by 48 hours demonstrated a trend toward independence at discharge. Such aggressive anticoagulation regimens may have the added benefit of maintaining candidacy for endovascular treatments by faster identification of patients’ responses to medical management. This preliminary research is likely underpowered and warrants further investigation to identify optimal treatment strategies for CST.